1983
DOI: 10.1002/jmv.1890110305
|View full text |Cite
|
Sign up to set email alerts
|

Candidate adenoviruses 40 and 41: Fastidious adenoviruses from human infant stool

Abstract: About 200 antigenically related adenoviruses were isolated from cases of infantile diarrhoea in the Netherlands and North-West Germany. The viruses were fastidious and failed to replicate serially in human diploid fibroblasts and in primary human embryonic kidney cells. A number of strains were established in HeLa, HEp-2, Graham (293), cynomolgus monkey kidney, and Chang conjunctival cells. The viruses were mammalian adenoviruses by the usual criteria. No relationship to the 39 known human adenovirus species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
0
5

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 28 publications
6
154
0
5
Order By: Relevance
“…Early surveys showed that the prevalence of Ad40 and Ad41 remained approximately equal (11,17). However, the findings in the present study were in line with recent studies that reported a decrease in the rate of isolation of Ad40 and a concomitant increase of Ad41 to become the predominant serotype associated with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Early surveys showed that the prevalence of Ad40 and Ad41 remained approximately equal (11,17). However, the findings in the present study were in line with recent studies that reported a decrease in the rate of isolation of Ad40 and a concomitant increase of Ad41 to become the predominant serotype associated with acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…These viruses (adenovirus strains 40 and 41) are known as the enteric adenoviruses, are responsible for 17% of all cases of infant diarrheas, 31 and have several characteristics which distinguish them from other human adenoviruses. The most notable of these is that, unlike other human adenoviruses, the fiber gene of these viruses contains two open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus types 40 and 41 can be distinguished from the other 39 human serotypes by serology, restriction enzyme cleavage analysis, polypeptide profiles and tissue culture growth characteristics Takiffet al, 1981 ;Uhnoo et al, 1983;Kidd, 1984). Although enteric adenoviruses are extremely difficult to propagate in conventional cell lines (de Jong et al, 1983) most strains can be successfully propagated in 293 cells which are human embryonic kidney cells transformed by Ad5 DNA (Graham et al, 1977).…”
Section: Introductionmentioning
confidence: 99%